2021
DOI: 10.1242/dmm.049023
|View full text |Cite
|
Sign up to set email alerts
|

Flow cytometry allows rapid detection of protein aggregates in cellular and zebrafish models of spinocerebellar ataxia 3

Abstract: Spinocerebellar ataxia-3 (SCA3, also Machado Joseph disease), is a neurodegenerative disease caused by inheritance of a CAG repeat expansion within the ATXN3 gene, resulting in polyglutamine (polyQ) repeat expansion within the ataxin-3 protein. In this study we have identified protein aggregates in both neuronal-like (SHSY5Y) cells and transgenic zebrafish expressing human ataxin-3 with expanded polyQ. We have adapted a previously reported flow cytometry methodology named flow cytometric analysis of inclusions… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 63 publications
(143 reference statements)
0
19
0
Order By: Relevance
“…Nuclei were identified and gated based on the intensity of UV fluorescence and relative size (forward scatter). The number of insoluble GFP particles, indicating insoluble ataxin‐3 particles, was analyzed based on GFP fluorescent intensity and forward scatter 47 . Gating of Triton‐X insoluble GFP + positive particles was performed by comparing populations to an un‐transfected control sample.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Nuclei were identified and gated based on the intensity of UV fluorescence and relative size (forward scatter). The number of insoluble GFP particles, indicating insoluble ataxin‐3 particles, was analyzed based on GFP fluorescent intensity and forward scatter 47 . Gating of Triton‐X insoluble GFP + positive particles was performed by comparing populations to an un‐transfected control sample.…”
Section: Methodsmentioning
confidence: 99%
“…Previously, we demonstrated that SH-SY5Y cells transiently transfected with EGFPfused human ataxin-3-84Q carry Triton-X insoluble protein aggregates that can be detected by a flow cytometry protocol called FloIT. 47 Upon immunostaining the stably expressing ataxin-3 cells for ataxin-3, the presence of cytoplasmic ataxin-3-positive puncta was revealed in cells expressing ataxin-3-28Q and -84Q (Figure 1D; white arrows). Automated quantification of the number of potential ataxin-3 protein aggregates (puncta with a diameter of 2.25-6 μm) within the images revealed that cells stably expressing ataxin-3-84Q had approximately double the number of puncta than cells expressing ataxin-3-28Q or an empty vector control (Figure 1E).…”
Section: A Sca3 Sh-sy5y Model Recapitulates Phenotypes Found In Human...mentioning
confidence: 98%
See 2 more Smart Citations
“…These models, with the full gene [95,102] or with a truncated gene, were used with the expanded CAG repeat tract [96][97][98]. They convincingly showed pathogenic features of polyQ diseases including aggregate formation, the toxicity of the mutant proteins, neurotransmission defects and progressive neuronal degeneration [92,[96][97][98]102,[165][166][167]. Additionally, they are excellent models with which to study the mechanisms underlying polyQ disease symptoms, find potential targets for therapeutic interventions, search for new interactomes and verify findings from other models or patients [95][96][97]101,167].…”
Section: Simple Model Organismsmentioning
confidence: 99%